Discussion of Hospital Working Capital: An Empirical Study - Drake, David F. (Journal of Accounting Research, 1977)
David F. Drake, Discussion of Hospital Working Capital: An Empirical Study, Journal of Accounting Research, Vol. 15, Studies on Measurement and Evaluation of the Economic Efficiency of Public and Private Nonprofit Institutions (1977), pp. 219-224